Hubungan Pengetahuan, Sikap, dan Dukungan Pendamping terhadap Lama Persalinan di Puskesmas Kemayoran - Wulandari, Wulandari; Jamilah, Jamilah (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Data on the health profile of DKI Jakarta province in 2020 shows that the number of maternal deaths was 117 mothers, an increase compared to 2019, namely 100 mothers. The maternal mortality rate in 2020 was 68.7 per 100,000 live births. For the Central Jakarta area in 2020, the maternal mortality rate was 10.4 per 100,000 live births or 13 cases out of 12,476 live births (Ministry of Health, 2020). One of the efforts to reduce the maternal mortality rate is normal birth care supported by Minister of Health Regulation no. 21 of 2021 Article 16 paragraph 2 concerning Maternity Health Services, one of which is providing affectionate care for the mother during childbirth, care provided by providing a companion who always accompanies the mother during labor (Utami & Fitriahadi, 2019). To determine the relationship between knowledge, attitudes and companion support on the length of labor at the Kemayoran Community Health Center in 2024. The type of research used is quantitative research with an observational analytical research design, using a cross sectional research approach. Sampling was carried out by purposive sampling with a sample of 60 people. Data techniques include univariate analysis using frequency distribution and bivariate analysis using statistical calculations from the SPSS program. There were 20 respondents who had poor knowledge of abnormal births, 9 people had poor knowledge of normal births, 8 respondents who had good knowledge of abnormal births, 9 people who had good knowledge of normal births. The chi square test obtained a p value = 0.001 (<0.05). There were 23 respondents who had a lack of attitude towards abnormal births, 13 people who had a positive attitude towards normal births, 5 respondents who had a good attitude towards abnormal births, and a good attitude towards normal births as many as 19 people. The chi square test obtained a p value = 0.01 (<0.05). Respondents who had less support for abnormal births were 19 people, less support for normal births were 5 people, respondents who had good support for abnormal births were 9 people, and good support for normal births were 27 people. The chi square test obtained a p value = 0.001 (<0.05). There is a significant influence of knowledge, attitudes and companion support on the length of labor with a p-value of 0.001 < 0.05. So it is hoped that health services and health workers, especially midwives, can play a supporting role in the birthing process. Keywords: Knowledge, Attitude, Companion Support, Normal Delivery ABSTRAK Data profil kesehatan provinsi DKI Jakarta tahun 2020 diketahui jumlah kematian ibu di sebesar 117 orang ibu, meningkat dibanding tahun 2019 yakni 100 orang ibu. Angka kematian ibu pada tahun 2020 adalah 68,7 tiap 100.000 kelahiran hidup. Untuk wilayah Jakarta Pusat tahun 2020 angka kematian ibu yaitu sebesar 10,4 per 100.000 kelahiran hidup atau sebanyak 13 kasus dari 12.476 kelahiran hidup (Kemenkes, 2020). Upaya menurunkan angka kematian ibu salah satunya asuhan persalinan normal dengan didukung Permenkes No. 21 Tahun 2021 Pasal 16 ayat 2 mengenai Pelayanan Kesehatan Persalinan salah satunya dengan memberikan asuhan sayang ibu selama persalinan, asuhan yang diberikan dengan menghadirkan pendamping yang selalu menemani ibu selama persalinan berlangsung (Utami & Fitriahadi, 2019). Mengetahui hubungan pengetahuan, sikap, dan dukungan pendamping terhadap lama persalinan di Puskesmas Kemayoran Tahun 2024. Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan desain penelitian analitik observasional, dengan menggunakan pendekatan penelitian cross sectional. Pengambilan sampel dilakukan dengan cara purposive sampling dengan sampel sebanyak 60 orang. Teknik data termasuk dalam analisis univariat menggunakan distribusi frekuensi dan analisis bivariat menggunakan perhitungan statistik program SPSS.  Responden yang mempunyai pengetahuan kurang persalinan abnormal sebanyak 20 orang, pengetahuan kurang persalinan normal sebanyak 9 orang, responden yang mempunyai pengetahuan baik persalinan abnormal sebanyak 8 orang pengetahuan baik persalinan normal sebanyak 9 orang. Uji uji chi square diperoleh nilai p= 0,001 (<0,05). Responden yang mempunyai sikap kurang persalinan abnormal sebanyak 23 orang, sikap kurang persalinan normal sebanyak 13 orang, responden yang mempunyai sikap baik persalinan abnormal sebanyak 5 orang, sikap baik persalinan normal sebanyak 19 orang. Uji chi square diperoleh nilai p= 0,01 (<0,05). Responden yang mempunyai dukungan kurang persalinan abnormal sebanyak 19 orang, dukungan kurang persalinan normal sebanyak 5 orang, responden yang mempunyai dukungan baik persalinan abnormal sebanyak 9 orang, dukungan baik persalinan normal sebanyak 27 orang. Uji uji chi square diperoleh nilai p= 0,001 (<0,05). Terdapat pengaruh yang signifikan pengetahuan, sikap dan dukungan pendamping terhadap lamanya persalinan dengan p-value 0,001 < 0,05. sehingga diharapkan untuk pelayanan kesehatan serta tenaga kesehatan khususnya bidan dapat menghadirkan peran pendamping dalam proses persalinan berlangsung. Kata Kunci: Pengetahuan, Sikap, Dukungan Pendamping, Persalinan Normal